Bipartite graph analyses reveal interdomain LGT involving ultrasmall prokaryotes and their divergent, membrane‐related proteins. (25th August 2016) - Jaffe, Alexander L.; Corel, Eduardo; Pathmanathan, Jananan Sylvestre; Lopez, Philippe; Bapteste, Eric
Summary: Based on their small size and genomic properties, ultrasmall prokaryotic groups like the Candidate Phyla Radiation have been proposed as possible symbionts dependent on other bacteria or archaea. In this study, we use a bipartite graph analysis to examine patterns of sequence similarity between draft and complete genomes from ultrasmall bacteria and other complete prokaryotic genomes, assessing whether the former group might engage in significant gene transfer (or even endosymbioses) with other community members. Our results provide preliminary evidence for many lateral gene transfers with other prokaryotes, including members of the archaea, and report the presence of divergent, membrane‐associated proteins among these ultrasmall taxa. In particular, these divergent genes were found in TM6 relatives of the intracellular parasite Babela massiliensis .